A naked ape would have fewer parasites - Pagel, M; Bodmer, W (2003)
Unusually among the mammals, humans lack an outer layer of protective fur or hair. We propose the hypothesis that humans evolved hairlessness to reduce parasite loads, especially ectoparasites that may carry disease. We suggest that hairlessness is maintained by these naturally selected benefits and by sexual selection operating on both sexes. Hairlessness is made possible in humans owing to their unique abilities to regulate their environment via fire, shelter and clothing. Clothes and shelters allow a more flexible response to the external environment than a permanent layer of fur and can be changed or cleaned if infested with parasites. Naked molerats, another hairless and non-aquatic mammal species, also inhabit environments in which ectoparasite transmission is expected to be high, but in which temperatures are closely regulated. Our hypothesis explains features of human hairlessnessm such as the marked sex difference in body hair, and its retention in the pubic regions - that are not explained by other theories.